2023
DOI: 10.5713/ab.21.0459
|View full text |Cite
|
Sign up to set email alerts
|

Position of Hungarian Merino among other Merinos, within-breed genetic similarity network and markers associated with daily weight gain

Abstract: In this study, we aimed to position the Hungarian Merino among other Merino-derived sheep breeds, explore the characteristics of our sampled animals' genetic similarity network within the breed, and highlight SNPs associated with daily weight-gain. MethodsHungarian Merino (n=138) was genotyped on Ovine SNP50 Bead Chip (Illumina, San Diego, CA) and positioned among 30 Merino and Merino-derived breeds (n=555). Population characteristics were obtained via PLINK, SVS, Admixture, and Treemix software, withinbreed n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
(38 reference statements)
1
4
0
1
Order By: Relevance
“…This study reveals that legume protein can influence lipid metabolism in ram lambs cells. Previous researchers (Li et al 2022;Zsolnai et al 2022) in pigs have shown similar results to the current study; it has been reported that feeding high protein diets can reduce lipogenesis activity.…”
Section: Lipid Regulationsupporting
confidence: 90%
See 1 more Smart Citation
“…This study reveals that legume protein can influence lipid metabolism in ram lambs cells. Previous researchers (Li et al 2022;Zsolnai et al 2022) in pigs have shown similar results to the current study; it has been reported that feeding high protein diets can reduce lipogenesis activity.…”
Section: Lipid Regulationsupporting
confidence: 90%
“…Protein interaction with the activity of this enzyme has been reported (Mushawwir et al 2020;Zsolnai et al 2022) that providing high protein in the ration can reduce the activity of fatty acid synthase (FFA). Decreased FFA enzyme expression reduces the rate of fat and adipose tissue anabolism.…”
Section: Lipid Regulationmentioning
confidence: 99%
“…Peter et al [ 78 ] observed in their study a short genetic distance between the two aforementioned breeds. HUG and POL were developed by crossing RAM, FLE, Russian Merinos, Merino Precoce, and Australian Merinos with the local population [ 36 , 79 , 80 ]. The TreeMix analysis also hinted at a possible gene flow from POL to European Mutton Merino breeds (MEI, IDF, and BDC) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…So herd A has animals sharing their state of genetic background with most of their herd companions. By comparing the overall patterns ( Figure 6 ) of herd A (n = 97) and the pattern obtained by the same methods on Hungarian Merino sheep (n = 138, Figure 4A [ 34 ]) it may be noted the appearance of a wheel-like structure. The reason for similar genetic net patterns of the Angus cattle and the Merino sheep [ 34 ] is that both are maintained for commercial reasons, so parameters for production traits are primordial.…”
Section: Resultsmentioning
confidence: 99%
“…By comparing the overall patterns ( Figure 6 ) of herd A (n = 97) and the pattern obtained by the same methods on Hungarian Merino sheep (n = 138, Figure 4A [ 34 ]) it may be noted the appearance of a wheel-like structure. The reason for similar genetic net patterns of the Angus cattle and the Merino sheep [ 34 ] is that both are maintained for commercial reasons, so parameters for production traits are primordial. Such wheel-like structures might be common in industrial breeds and might not be characteristic for the breeds where maintenance of diversity is of cardinal importance.…”
Section: Resultsmentioning
confidence: 99%